Preparation method and application of polydimethylsiloxane super-hydrophobic anti-icing and deicing material
The traditional deicing method is solved by spraying modified CNTs/SiO2 composite coating solution on the porous foam of polydimethylsiloxane and carbon nanotubes to form polydimethylsiloxane superhydrophobic anti-icing deicing material. The problems of low efficiency and easy material damage have achieved improvements in the photothermal stability of the material and the deicing and defrosting performance.
Patent Information
- Application Number
- CN202411484696.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-23
AI Technical Summary
Traditional deicing methods are inefficient, costly, and polluted the environment. The surface of superhydrophobic materials is prone to damage, resulting in reduced superhydrophobicity and photothermal properties.
PDMS/CNTs porous foam was prepared by polydimethylsiloxane and carbon nanotubes, and spray-modified using CNTs/SiO2 superhydrophobic composite coating solution to form polydimethylsiloxane superhydrophobic anti-icing deicing material .
The material's photothermal stability, superhydrophobicity, corrosion resistance and excellent deicing and defrosting properties are achieved, and the material's wear resistance and ice melting effect are improved.
Smart Images

Figure CN119286394A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of polydimethylsiloxane coatings and anti-icing coatings for the fields of ships, airplanes, high-speed railways, marine engineering, etc. More specifically, the present invention relates to a preparation method and application of a polydimethylsiloxane super-hydrophobic anti-icing and deicing material. Background Art
[0002] Icing is a common natural phenomenon, but ice formation and ice accumulation on the surface of equipment can cause a lot of economic and energy losses, and even threaten people's lives and property. Therefore, it is important and urgent to study reliable, efficient and economical anti-icing technology.
[0003] Traditional deicing solutions include mechanical deicing, pulse deicing and chemical deicing. However, these deicing methods are limited in practical applications due to low efficiency, high cost and environmental pollution. In recent years, photothermal super-hydrophobic materials with super-hydrophobicity and photothermal conversion capabilities are regarded as a new generation of anti-icing and deicing technology because of their advantages of both passive deicing and active deicing. Summary of the invention
[0004] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.
[0005] In view of the fact that the surface of super-hydrophobic materials is easily damaged, which significantly reduces their super-hydrophobicity and destroys their photothermal performance, a porous foam prepared with PDMS and CNTs is used as the skeleton surface to spray a modified CNTs / SiO2 composite coating solution. It is expected that the material will have good photothermal performance and photothermal stability, super-hydrophobicity, corrosion resistance and excellent deicing and defrosting performance.
[0006] In order to achieve these purposes and other advantages according to the present invention, a method for preparing a polydimethylsiloxane super-hydrophobic anti-icing and deicing material is provided, which is characterized by comprising:
[0007] PDMS / CNTs porous foam was prepared using polydimethylsiloxane and carbon nanotubes. The PDMS / CNTs porous foam was spray-modified using a CNTs / SiO2 super-hydrophobic composite coating solution, and a polydimethylsiloxane super-hydrophobic anti-icing and de-icing material was obtained after curing.
[0008] Preferably, the method comprises the following steps:
[0009] Step 1: Mix polydimethylsiloxane, a curing agent and carbon nanotubes and stir them evenly, then place them in a vacuum drying oven to remove air bubbles;
[0010] Step 2: Weigh a certain amount of sodium chloride and mix it with the mixture obtained in step 1 in a certain proportion, put it into a mold, compact it, and then place it in a drying oven to solidify; after taking out the mold, place the solidified sample in a solvent, perform ultrasound in an ultrasonic machine, so that all the sodium chloride particles are precipitated, and then cut it into blocks to obtain PDMS / CNTs porous foam;
[0011] Step 3, respectively taking a certain amount of nano-SiO2 and carbon nanotubes, and then respectively adding a certain amount of 1H, 1H, 2H, 2H-perfluorodecyltrimethoxysilane, respectively adding a certain amount of anhydrous ethanol, respectively adding hydrochloric acid to adjust the pH value, and then respectively performing magnetic stirring and ultrasonication, and then drying and grinding the obtained mixtures to obtain modified SiO2 nanoparticles and modified carbon nanotubes;
[0012] Step 4: adding the modified SiO2 nanoparticles, modified carbon nanotubes, binder and curing agent obtained in step 3 into the solvent in a certain proportion, and then stirring with magnetic force to obtain a CNTs / SiO2 super-hydrophobic composite coating solution;
[0013] Step 5: Spray the CNTs / SiO2 super-hydrophobic composite coating solution obtained in step 4 onto the surface of the PDMS / CNTs porous foam obtained in step 2, and then dry and solidify the sample to obtain a polydimethylsiloxane super-hydrophobic anti-icing and de-icing material.
[0014] Preferably, in the step 1, the ratio of polydimethylsiloxane, curing agent and CNTs is 50:5:1; the polydimethylsiloxane is component A of Dow Corning 184-PDMS, and the curing agent is component B of Dow Corning 184-PDMS.
[0015] Preferably, in the step 2, the ratio of sodium chloride to the mixture is 10:1, the curing temperature is 60-90° C., the curing time is 6-24 hours, and the solvent used in the solvent immersion ultrasound after curing is deionized water.
[0016] Preferably, in step three, the mass volume ratio of nano-SiO2, 1H,1H,2H,2H-perfluorodecyltrimethoxysilane and anhydrous ethanol is 4g:1.2g:40mL, and the pH is adjusted to 5 with hydrochloric acid.
[0017] Preferably, in step three, the mass volume ratio of carbon nanotubes, 1H,1H,2H,2H-perfluorodecyltrimethoxysilane and anhydrous ethanol is 2.5g:0.8g:100mL, and the pH is adjusted to 3 with hydrochloric acid.
[0018] Preferably, in step three, the magnetic stirring time is 1 to 3 hours, and the ultrasonic time is 10 to 50 minutes.
[0019] Preferably, in the step 4, the solvent is n-hexane, the binder is polydimethylsiloxane, the polydimethylsiloxane is component A of Dow Corning 184-PDMS, and the curing agent is component B of Dow Corning 184-PDMS;
[0020] The mass volume ratio of the total mass of the modified SiO2 nanoparticles and the modified carbon nanotubes to the n-hexane, the polydimethylsiloxane and the curing agent is 0.1 g:10 ml:0.1 g:0.01 g; and the magnetic stirring time is 1 to 3 hours.
[0021] Preferably, in step five, the curing temperature is 80° C. and the curing time is 1 to 2 hours.
[0022] The invention discloses an application of a polydimethylsiloxane super-hydrophobic anti-icing and de-icing material. The polydimethylsiloxane super-hydrophobic anti-icing and de-icing material is applied to the hydrophobicity and anti-icing and de-icing of the surfaces of ships, airplanes, high-speed railways and marine engineering projects.
[0023] In order to further improve the hydrophobic properties of the polydimethylsiloxane superhydrophobic anti-icing and deicing material, the modification method of the modified SiO2 nanoparticles in step 3 is replaced by:
[0024] A certain amount of nano-SiO2 is ultrasonically dispersed in anhydrous ethanol to obtain a nano-SiO2 dispersion, and ammonia water is added to adjust the pH value to 9-10, and 3-aminopropyltriethoxysilane is added dropwise while stirring, and then magnetic stirring is performed to obtain a dispersion A; methyl methacrylate is added to deionized water, sodium dodecyl sulfate is added, and ultrasonic dispersion is performed at an ultrasonic frequency of 45-60kH, and the ultrasonic dispersion is performed for 20-60min to obtain a dispersion B; wherein the volume mass ratio of nano-SiO2, anhydrous ethanol, and 3-aminopropyltriethoxysilane is 5-9g:50-80mL:0.5-1.5g; the mass volume ratio of methyl methacrylate, deionized water, and sodium dodecyl sulfate is 2-5g:60-100mL:0.5-1g;
[0025] After the dispersion A is allowed to stand for 6 to 12 hours, the temperature is raised to 80 to 90°C, and then the mixture is continuously stirred at a speed of 400 to 600 rpm, sodium bicarbonate is added as a pH buffer and sodium persulfate is added as an initiator, and then a dispersion B equal in volume to the dispersion A is added, and the stirring is stopped after reacting for 1 to 3 hours, and the mixture is cooled to room temperature, centrifuged, filtered, and the solid is dried at a temperature of 40 to 80°C to obtain modified SiO2 nanoparticles. The mass volume ratio of the dispersion A, sodium bicarbonate and sodium persulfate is 50 to 80 mL: 0.2 to 0.8 g: 0.3 to 0.5 g.
[0026] Then the obtained mixture is dried and ground respectively to obtain modified SiO2 nanoparticles.
[0027] The present invention includes at least the following beneficial effects: the polydimethylsiloxane super-hydrophobic anti-icing and de-icing material prepared by the present invention can perform photothermal deicing and defrosting, and has excellent photothermal stability, excellent super-hydrophobicity, good corrosion resistance, and good wear resistance. The polydimethylsiloxane super-hydrophobic anti-icing and de-icing material prepared by the present invention has good ice melting effect and defrosting ability.
[0028] In the preparation process of the polydimethylsiloxane super-hydrophobic anti-icing and de-icing material of the present invention, a CNTs / SiO2 super-hydrophobic composite coating solution with modified SiO2 nanoparticles and modified carbon nanotubes as main raw materials is used, wherein the modified SiO2 nanoparticles adopt two modification methods, one is to hydrophobically modify nano-SiO2 with 1H, 1H, 2H, 2H-perfluorodecyltrimethoxysilane to prepare modified SiO2 nanoparticles with hydrophobic properties, and the other is to prepare a CNTs / SiO2 super-hydrophobic composite coating solution with modified SiO2 nanoparticles and modified carbon nanotubes. After the coating solution was sprayed on the surface of PDMS / CNTs porous foam and cured, the prepared polydimethylsiloxane superhydrophobic anti-icing and deicing material had excellent superhydrophobic properties; the other method was to use 3-aminopropyltriethoxysilane and methyl methacrylate to hydrophobically modify nano-SiO2. The results showed that the modified SiO2 nanoparticles prepared by using 3-aminopropyltriethoxysilane and methyl methacrylate as the raw material of CNTs / SiO2 superhydrophobic composite coating solution further improved the superhydrophobic properties of the polydimethylsiloxane superhydrophobic anti-icing and deicing material.
[0029] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is an electron microscope image of the PDMS / CNTs porous foam prepared in step 2 of Example 3;
[0031] Figure 2 This is an electron microscope image of the polydimethylsiloxane super-hydrophobic anti-icing and de-icing material prepared in step 2 of Example 3;
[0032] Figure 3 The photothermal temperature rise diagrams of Examples 1 to 6, PDMS / CNTs and pure PDMS porous foams;
[0033] Figure 4 This is a graph of 10 photothermal on / off cycles of Example 3;
[0034] Figure 5 This is a graph of ice melting time under different light intensities in Example 3;
[0035] Figure 6 This is a diagram of the defrosting time process of Example 3 under different light intensities. DETAILED DESCRIPTION
[0036] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.
[0037] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.
[0038] Embodiment 1:
[0039] A method for preparing a polydimethylsiloxane super-hydrophobic anti-icing and de-icing material, comprising:
[0040] Step 1, preparation of PDMS / CNTs porous foam material: first, 10g polydimethylsiloxane (PDMS), 0.2g carbon nanotubes (CNTs), and 1g curing agent were mixed evenly, then 100g NaCl was added and stirred evenly again, put into a mold and then placed in a drying oven at 80°C for 12 hours. Polydimethylsiloxane is the A component of Dow Corning 184-PDMS, and the curing agent is the B component of Dow Corning 184-PDMS.
[0041] Step 2: Soak the PDMS / CNTs cured in step 1 in an aqueous solution and ultrasonicate for 7 days, changing the water every 2 hours until the NaCl template is completely removed to obtain a PDMS / CNTs porous foam, i.e., PC, which is cut into 30 mm × 30 mm × 3 mm sheets.
[0042] Step 3, preparation of surface coating materials, first add 4g of nano-SiO2 (diameter about 10-20nm, Aladdin, 99.5%) and 1.2g of 1H,1H,2H,2H-perfluorodecylsilane (purchased from Shanghai McLean Biochemical Co., Ltd.) to 40ml of anhydrous ethanol, use hydrochloric acid to adjust the pH to 5, then stir magnetically for 2h, put the resulting slurry into a drying oven at 100°C for drying and grinding to obtain modified nano-SiO2 for use. Add 2.5g of carbon nanotubes and 0.8g of 1H,1H,2H,2H-perfluorodecylsilane to 100ml of anhydrous ethanol, add hydrochloric acid to adjust the pH to 3, then stir magnetically for 2 hours, ultrasonicate for 30min, and finally put it into an oven at 80°C for drying and grinding for use, thus obtaining modified carbon nanotubes.
[0043] Step 4: Add 0.1g PDMS and 0.01g curing agent to 10ml n-hexane, and then stir magnetically for 30min, polydimethylsiloxane is component A of Dow Corning 184-PDMS, and the curing agent is component B of Dow Corning 184-PDMS. Subsequently, 0.1g of modified SiO2 and modified carbon nanotubes were added to the solution, wherein the masses of modified SiO2 and modified carbon nanotubes were 100mg and 0mg respectively, and then stirred magnetically for 2 hours to obtain a CNTs / SiO2 super-hydrophobic composite coating solution.
[0044] Step 5: Spray the CNTs / SiO2 super-hydrophobic composite coating solution obtained in step 4 onto the surface of the PDMS / CNTs porous foam obtained in step 2, and then place the PDMS / CNTs porous foam in an oven at 80°C for curing for 2 hours to obtain a polydimethylsiloxane super-hydrophobic anti-icing and deicing material, which is called PCSC-0%.
[0045] Embodiment 2:
[0046] A method for preparing a polydimethylsiloxane super-hydrophobic anti-icing and deicing material, comprising:
[0047] Step 1, preparation of PDMS / CNTs porous foam material: first, 10g PDMS, 0.2g CNTs, and 1g curing agent were mixed evenly, then 100g NaCl was added and stirred evenly again, put into a mold, and then placed in a drying oven at 80°C for curing for 12 hours. Polydimethylsiloxane is the A component of Dow Corning 184-PDMS, and the curing agent is the B component of Dow Corning 184-PDMS.
[0048] Step 2: Soak the cured PDMS / CNTs in an aqueous solution and ultrasonicate for 7 days, changing the water every 2 hours until the NaCl template is completely removed to obtain a PDMS / CNTs porous foam, i.e., PC, which is cut into 30 mm × 30 mm × 3 mm sheets.
[0049] Step 3, preparation of surface coating materials, first add 4g of nano-SiO2 (diameter about 10-20nm, Aladdin, 99.5%) and 1.2g of 1H,1H,2H,2H-perfluorodecylsilane (purchased from Shanghai McLean Biochemical Co., Ltd.) to 40ml of anhydrous ethanol, use hydrochloric acid to adjust the pH to 5, then stir magnetically for 2h, put the resulting slurry into a drying oven at 100°C for drying and grinding to obtain modified nano-SiO2 for use. Add 2.5g of carbon nanotubes and 0.8g of 1H,1H,2H,2H-perfluorodecylsilane to 100ml of anhydrous ethanol, add hydrochloric acid to adjust the pH to 3, then stir magnetically for 2 hours, ultrasonicate for 30min, and finally put it into an oven at 80°C for drying and grinding for use, thus obtaining modified carbon nanotubes.
[0050] Step 4: Add 0.1g PDMS and 0.01g curing agent to 10ml n-hexane, and then stir magnetically for 30min, polydimethylsiloxane is component A of Dow Corning 184-PDMS, and the curing agent is component B of Dow Corning 184-PDMS. Then add 0.1g of modified SiO2 and modified carbon nanotubes to the solution, wherein the masses of modified SiO2 and modified carbon nanotubes are 85mg and 15mg respectively, and then stir magnetically for 2 hours to obtain a CNTs / SiO2 super-hydrophobic composite coating solution.
[0051] Step 5: Spray the CNTs / SiO2 super-hydrophobic composite coating solution obtained in step 4 onto the surface of the PDMS / CNTs foam obtained in step 2, and then put it into an oven for curing at 80°C for 2 hours to obtain a polydimethylsiloxane super-hydrophobic anti-icing and deicing material, which is called PCSC-15%.
[0052] Embodiment 3:
[0053] A method for preparing a polydimethylsiloxane super-hydrophobic anti-icing and de-icing material, comprising:
[0054] Step 1, preparation of PDMS / CNTs porous foam material: first, 10g PDMS, 0.2g CNTs, and 1g curing agent were mixed evenly, then 100g NaCl was added and stirred evenly again, put into a mold, and then placed in a drying oven at 80°C for curing for 12 hours. Polydimethylsiloxane is the A component of Dow Corning 184-PDMS, and the curing agent is the B component of Dow Corning 184-PDMS.
[0055] Step 2: Soak the cured PDMS / CNTs in an aqueous solution and perform ultrasonic treatment for 7 days, changing the water every 2 hours until the NaCl template is completely removed to obtain a PDMS / CNTs porous foam, i.e., PC, which is cut into 30 mm × 30 mm × 3 mm sheets. The electron microscope image of the PDMS / CNTs porous foam prepared in this example is shown in FIG. Figure 1 As shown, from Figure 1 It can be seen that the pores of the prepared PDMS / CNTs porous foam are evenly distributed, and its surface is relatively smooth through high magnification.
[0056] Step 3, preparation of surface coating materials, first add 4g of nano-SiO2 (diameter about 10-20nm, Aladdin, 99.5%) and 1.2g of 1H,1H,2H,2H-perfluorodecylsilane (purchased from Shanghai McLean Biochemical Co., Ltd.) to 40ml of anhydrous ethanol, use hydrochloric acid to adjust the pH to 5, then stir magnetically for 2h, put the resulting slurry into a drying oven at 100°C for drying and grinding to obtain modified nano-SiO2 for use. Add 2.5g of carbon nanotubes and 0.8g of 1H,1H,2H,2H-perfluorodecylsilane to 100ml of anhydrous ethanol, add hydrochloric acid to adjust the pH to 3, then stir magnetically for 2 hours, ultrasonicate for 30min, and finally put it into an oven at 80°C for drying and grinding for use, thus obtaining modified carbon nanotubes.
[0057] Step 4: Add 0.1g PDMS and 0.01g curing agent to 10ml n-hexane, and then stir magnetically for 30min, where polydimethylsiloxane is component A of Dow Corning 184-PDMS, and the curing agent is component B of Dow Corning 184-PDMS. Then add 0.1g of SiO2 and carbon nanotubes to the solution, where the masses of SiO2 and carbon nanotubes are 65mg and 35mg respectively, and then stir magnetically for 2 hours to obtain a CNTs / SiO2 super-hydrophobic composite coating solution.
[0058] Step 5: Spray the CNTs / SiO2 super-hydrophobic composite coating solution obtained in step 4 onto the surface of the PDMS / CNTs porous foam obtained in step 2, and then put it into an oven at 80°C for curing for 2 hours to obtain a polydimethylsiloxane super-hydrophobic anti-icing and deicing material, which is called PCSC-35%. The surface morphology of the polydimethylsiloxane super-hydrophobic anti-icing and deicing material sample prepared in this embodiment is shown in the electron microscope image as follows: Figure 2 As shown, from Figure 2 It can be seen that the surface of the sample is covered with a layer of rough micro-nanostructure, which can capture air and form an air-liquid interface when in contact with liquid, making the sample surface superhydrophobic.
[0059] Embodiment 4:
[0060] A method for preparing a polydimethylsiloxane super-hydrophobic anti-icing and deicing material, comprising:
[0061] Step 1, preparation of porous PDMS / CNTs foam material: first, 10g PDMS, 0.2g CNTs, and 1g curing agent were mixed evenly, then 100g NaCl was added and stirred evenly again, put into a mold, and then placed in a drying oven at 80°C for curing for 12 hours. Polydimethylsiloxane is the A component of Dow Corning 184-PDMS, and the curing agent is the B component of Dow Corning 184-PDMS.
[0062] Step 2: Soak the cured PDMS / CNTs in an aqueous solution and ultrasonicate for 7 days, changing the water every 2 hours until the NaCl template is completely removed to obtain a PDMS / CNTs porous foam, i.e., PC, which is cut into 30 mm × 30 mm × 3 mm sheets.
[0063] Step 3, preparation of surface coating materials, first add 4g of nano-SiO2 (diameter about 10-20nm, Aladdin, 99.5%) and 1.2g of 1H,1H,2H,2H-perfluorodecylsilane (purchased from Shanghai McLean Biochemical Co., Ltd.) to 40ml of anhydrous ethanol, use hydrochloric acid to adjust the pH to 5, then stir magnetically for 2h, put the resulting slurry into a drying oven at 100°C for drying and grinding to obtain modified nano-SiO2 for use. Add 2.5g of carbon nanotubes and 0.8g of 1H,1H,2H,2H-perfluorodecylsilane to 100ml of anhydrous ethanol, add hydrochloric acid to adjust the pH to 3, then stir magnetically for 2 hours, ultrasonicate for 30min, and finally put it into an oven at 80°C for drying and grinding for use, thus obtaining modified carbon nanotubes.
[0064] Step 4: Add 0.1 g PDMS and 0.01 g curing agent to 10 ml n-hexane, and then stir magnetically for 30 min. Polydimethylsiloxane is component A of Dow Corning 184-PDMS, and the curing agent is component B of Dow Corning 184-PDMS. Then, add 0.1 g of SiO2 and carbon nanotubes to the solution, wherein the mass of SiO2 and carbon nanotubes is 50 mg and 50 mg respectively, and then stir magnetically for 2 hours.
[0065] Step 5: spray the solution obtained in step 4 onto the surface of the PDMS / CNTs foam obtained in step 2, and then put it into an oven for curing at 80° C. for 2 hours to obtain a polydimethylsiloxane superhydrophobic anti-icing and deicing material, which is called PCSC-50%.
[0066] Embodiment 5:
[0067] A method for preparing a polydimethylsiloxane super-hydrophobic anti-icing and de-icing material, comprising:
[0068] Step 1, preparation of porous PDMS / CNTs foam material: first, 10g PDMS, 0.2g CNTs, and 1g curing agent were mixed evenly, then 100g NaCl was added and stirred evenly again, put into a mold, and then placed in a drying oven at 80°C for curing for 12 hours. Polydimethylsiloxane is the A component of Dow Corning 184-PDMS, and the curing agent is the B component of Dow Corning 184-PDMS.
[0069] Step 2: Soak the cured PDMS / CNTs in an aqueous solution and ultrasonicate for 7 days, changing the water every 2 hours until the NaCl template is completely removed to obtain a PDMS / CNTs porous foam, i.e., PC, which is cut into 30 mm × 30 mm × 3 mm sheets.
[0070] Step 3, preparation of surface coating materials, first add 4g of nano-SiO2 (diameter about 10-20nm, Aladdin, 99.5%) and 1.2g of 1H,1H,2H,2H-perfluorodecylsilane (purchased from Shanghai McLean Biochemical Co., Ltd.) to 40ml of anhydrous ethanol, use hydrochloric acid to adjust the pH to 5, then stir magnetically for 2h, put the resulting slurry into a drying oven at 100°C for drying and grinding to obtain modified nano-SiO2 for use. Add 2.5g of carbon nanotubes and 0.8g of 1H,1H,2H,2H-perfluorodecylsilane to 100ml of anhydrous ethanol, add hydrochloric acid to adjust the pH to 3, then stir magnetically for 2 hours, ultrasonicate for 30min, and finally put it into an oven at 80°C for drying and grinding for use, thus obtaining modified carbon nanotubes.
[0071] Step 4: Add 0.1 g PDMS and 0.01 g curing agent to 10 ml n-hexane, and then stir magnetically for 30 min. Then add 0.1 g SiO2 and carbon nanotubes, where the mass of SiO2 and carbon nanotubes is 35 mg and 65 mg respectively, to the solution, and then stir magnetically for 2 hours.
[0072] Step 5: spray the solution obtained in step 4 onto the surface of the PDMS / CNTs foam obtained in step 2, and then put it into an oven for curing at 80° C. for 2 hours to obtain a polydimethylsiloxane superhydrophobic anti-icing and deicing material, which is called PCSC-65%.
[0073] Embodiment 6:
[0074] A method for preparing a polydimethylsiloxane super-hydrophobic anti-icing and deicing material, comprising:
[0075] Step 1, preparation of porous PDMS / CNTs foam material: first, 10g PDMS, 0.2g CNTs, and 1g curing agent were mixed evenly, then 100g NaCl was added and stirred evenly again, put into a mold, and then placed in a drying oven at 80°C for curing for 12 hours. Polydimethylsiloxane is the A component of Dow Corning 184-PDMS, and the curing agent is the B component of Dow Corning 184-PDMS.
[0076] Step 2: Soak the cured PDMS / CNTs in an aqueous solution and ultrasonicate for 7 days, changing the water every 2 hours until the NaCl template is completely removed to obtain a PDMS / CNTs porous foam, i.e., PC, which is cut into 30 mm × 30 mm × 3 mm sheets.
[0077] Step 3, preparation of surface coating materials, first add 4g of nano-SiO2 (diameter about 10-20nm, Aladdin, 99.5%) and 1.2g of 1H,1H,2H,2H-perfluorodecylsilane (purchased from Shanghai McLean Biochemical Co., Ltd.) to 40ml of anhydrous ethanol, use hydrochloric acid to adjust the pH to 5, then stir magnetically for 2h, put the resulting slurry into a drying oven at 100°C for drying and grinding to obtain modified nano-SiO2 for use. Add 2.5g of carbon nanotubes and 0.8g of 1H,1H,2H,2H-perfluorodecylsilane to 100ml of anhydrous ethanol, add hydrochloric acid to adjust the pH to 3, then stir magnetically for 2 hours, ultrasonicate for 30min, and finally put it into an oven at 80°C for drying and grinding for use, thus obtaining modified carbon nanotubes.
[0078] Step 4: Add 0.1 g PDMS and 0.01 g curing agent to 10 ml n-hexane, and then stir magnetically for 30 min, where polydimethylsiloxane is component A of Dow Corning 184-PDMS, and the curing agent is component B of Dow Corning 184-PDMS. Then, add 0.1 g of SiO2 and carbon nanotubes to the solution, where the masses of SiO2 and carbon nanotubes are 0 mg and 100 mg, respectively, and stir magnetically for 2 hours.
[0079] Step 5: spray the solution obtained in step 4 onto the surface of the PDMS / CNTs foam obtained in step 2, and then put it into an oven for curing at 80° C. for 2 hours to obtain a polydimethylsiloxane superhydrophobic anti-icing and deicing material, which is called PCSC-100%.
[0080] Example 7
[0081] This embodiment provides a method for preparing a polydimethylsiloxane superhydrophobic anti-icing and deicing material. Compared with Example 3, the modified SiO2 nanoparticles are replaced in step 3, the modification method of the modified carbon nanotubes remains unchanged, and the process parameters of the remaining steps are the same as those of Example 3; wherein the modification method of the replaced modified SiO2 nanoparticles is:
[0082] 5 g of nano-SiO2 was ultrasonically dispersed in 60 mL of anhydrous ethanol to obtain a nano-SiO2 dispersion, and ammonia water was added to adjust the pH value to 9. 1.5 g of 3-aminopropyltriethoxysilane was added dropwise while stirring, and then magnetic stirring was performed to obtain dispersion A; 3 g of methyl methacrylate was added to 60 mL of deionized water, and 0.5 g of sodium dodecyl sulfate was added, and ultrasonic dispersion was performed at an ultrasonic frequency of 60 kH for 40 min to obtain dispersion B;
[0083] Take 50 mL of dispersion A, let it stand for 12 hours, then heat it to 80°C, and then continue stirring at 400 rpm, add 0.3 g of sodium bicarbonate as a pH buffer and 0.3 g of sodium persulfate as an initiator, and then add 50 mL of dispersion B. After reacting for 2 hours, stop stirring and cool to room temperature, centrifuge, filter, and dry the solid at 60°C to obtain modified SiO2 nanoparticles.
[0084] Example 8
[0085] This embodiment provides a method for preparing a polydimethylsiloxane superhydrophobic anti-icing and deicing material. Compared with Example 3, the modified SiO2 nanoparticles are replaced in step 3, the modification method of the modified carbon nanotubes remains unchanged, and the process parameters of the remaining steps are the same as those of Example 3; wherein the modification method of the replaced modified SiO2 nanoparticles is:
[0086] 8 g of nano-SiO2 was ultrasonically dispersed in 100 mL of anhydrous ethanol to obtain a nano-SiO2 dispersion, and ammonia water was added to adjust the pH value to 9. 1.5 g of 3-aminopropyltriethoxysilane was added dropwise while stirring, and then magnetic stirring was performed to obtain dispersion A; 5 g of methyl methacrylate was added to 100 mL of deionized water, and 0.5 g of sodium dodecyl sulfate was added, and ultrasonic dispersion was performed at an ultrasonic frequency of 60 kH for 40 min to obtain dispersion B;
[0087] Take 50 mL of dispersion A that has been allowed to stand for 12 hours, heat it to 80°C, and then continue stirring at 600 rpm, add 0.8 g of sodium bicarbonate as a pH buffer and 0.5 g of sodium persulfate as an initiator, and then add 50 mL of dispersion B. After reacting for 3 hours, stop stirring and cool to room temperature, centrifuge, filter, and dry the solid at 60°C to obtain modified SiO2 nanoparticles.
[0088] The present invention provides a method for testing the super-hydrophobic properties of the polydimethylsiloxane super-hydrophobic anti-icing and de-icing materials prepared in Examples 1 to 8, comprising:
[0089] The present invention uses a contact angle meter to test the contact angle and sliding angle of Examples 1 to 8. The test conditions are to drop 10 μl of deionized water on the sample surface through a syringe, measure the contact angle of the droplet on the sample surface through the contact angle meter, and then control the rotation of the contact angle meter workbench and record the angle of the droplet when it slides down to obtain the rolling angle of the sample. Each material is repeated 3 to 5 times. The results are shown in Table 1.
[0090] Table 1
[0091]
[0092]
[0093] As can be seen from Table 1, compared with the contact angle of PC, and the droplet cannot slide on the PC surface, Examples 1 to 6 all have a contact angle of more than 150° and a sliding angle of less than 10°, which indicates that they have excellent superhydrophobic properties.
[0094] At the same time, in Example 7 and Example 8, the contact angle of deionized water reached a maximum of 167.4°, and the rolling angle of deionized water was reduced to 2.7°, indicating that after Example 7 and Example 8 used modified SiO2 nanoparticles modified with 3-aminopropyltriethoxysilane and methyl methacrylate as the raw materials of the CNTs / SiO2 super-hydrophobic composite coating solution, the super-hydrophobic properties of the polydimethylsiloxane super-hydrophobic anti-icing and de-icing material were further improved.
[0095] The present invention uses a xenon lamp light source (PLS-SXE300), an infrared thermometer and an optical power meter (PL-MW2000) to conduct a photothermal heating experiment on Examples 1 to 6. The optical power meter is used to adjust the xenon lamp light source to a 1-sun light intensity. The results are as follows: Figure 3 It can be seen that the material has excellent light and heat performance. And through 10 times of light and off cycle test, such as Figure 4 As shown, it can be seen that the material has excellent light and heat stability. Then, a refrigeration platform, a xenon lamp light source, and an optical power meter were used to perform a de-icing test on Experimental Example 3. The test conditions were as follows: on a -20°C refrigeration platform, the test sample was placed on the refrigeration platform, and 10 μl of deionized water was dripped onto the sample surface to make it completely frozen. Then, the xenon lamp light source was turned on, and the light intensity was adjusted using an optical power meter. Then, the timing was started after the light source was irradiated onto the sample surface, and the ice was completely melted into liquid. The timing was stopped to obtain the ice melting time. Figure 5 It can be seen that the material has excellent deicing performance. Figure 5 The horizontal axis is light intensity and the vertical axis is time.
[0096] The present invention uses a xenon lamp light source, an optical power meter and a refrigeration platform to perform a defrosting test on Example 3. The temperature of the refrigeration platform is adjusted to -20°C, and the sample is placed on the refrigeration platform, and then naturally frosted in an environment with an ambient humidity of 80%. After the surface of the sample is completely covered with frost, the xenon lamp light source is turned on and the light intensity is adjusted to 1 sun light intensity and 0.5 sun light intensity. The results are shown in Figure 6 It can be seen that the material has excellent defrosting performance.
[0097] The number of devices and processing scales described here are used to simplify the description of the present invention. Applications, modifications and variations of the present invention will be obvious to those skilled in the art.
[0098] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.
Claims
1. A method for preparing a polydimethylsiloxane super-hydrophobic anti-icing and deicing material, characterized in that: include: PDMS / CNTs porous foam was prepared using polydimethylsiloxane and carbon nanotubes. The PDMS / CNTs porous foam was spray-modified using a CNTs / SiO2 super-hydrophobic composite coating solution, and a polydimethylsiloxane super-hydrophobic anti-icing and de-icing material was obtained after curing.
2. The method for preparing the polydimethylsiloxane super-hydrophobic anti-icing and deicing material according to claim 1, characterized in that: The following steps are involved: Step 1: Mix polydimethylsiloxane, a curing agent and carbon nanotubes and stir them evenly, then place them in a vacuum drying oven to remove air bubbles; Step 2: Weigh a certain amount of sodium chloride and mix it with the mixture obtained in step 1 in a certain proportion, put it into a mold, compact it, and then place it in a drying oven to solidify; after taking out the mold, place the solidified sample in a solvent, perform ultrasound in an ultrasonic machine, so that all the sodium chloride particles are precipitated, and then cut it into blocks to obtain PDMS / CNTs porous foam; Step 3, respectively taking a certain amount of nano-SiO2 and carbon nanotubes, and then respectively adding a certain amount of 1H, 1H, 2H, 2H-perfluorodecyltrimethoxysilane, respectively adding a certain amount of anhydrous ethanol, respectively adding hydrochloric acid to adjust the pH value, and then respectively performing magnetic stirring and ultrasonication, and then drying and grinding the obtained mixtures to obtain modified SiO2 nanoparticles and modified carbon nanotubes; Step 4: adding the modified SiO2 nanoparticles, modified carbon nanotubes, binder and curing agent obtained in step 3 into the solvent in a certain proportion, and then stirring with magnetic force to obtain a CNTs / SiO2 super-hydrophobic composite coating solution; Step 5: Spray the CNTs / SiO2 super-hydrophobic composite coating solution obtained in step 4 onto the surface of the PDMS / CNTs porous foam obtained in step 2, and then dry and solidify the sample to obtain a polydimethylsiloxane super-hydrophobic anti-icing and de-icing material.
3. The method for preparing the polydimethylsiloxane super-hydrophobic anti-icing and deicing material according to claim 2, characterized in that: In the step 1, the ratio of polydimethylsiloxane, curing agent and CNTs is 50:5:1; the polydimethylsiloxane is component A of Dow Corning 184-PDMS, and the curing agent is component B of Dow Corning 184-PDMS.
4. The method for preparing the polydimethylsiloxane super-hydrophobic anti-icing and deicing material according to claim 2, characterized in that: In the step 2, the ratio of sodium chloride to the mixture is 10:1, the curing temperature is 60-90° C., the curing time is 6-24 hours, and the solvent used for ultrasonic immersion after curing is deionized water.
5. The method for preparing the polydimethylsiloxane super-hydrophobic anti-icing and deicing material according to claim 2, characterized in that: In the step 3, the mass volume ratio of nano-SiO2, 1H,1H,2H,2H-perfluorodecyltrimethoxysilane and anhydrous ethanol is 4g:1.2g:40mL, and the pH is adjusted to 5 with hydrochloric acid.
6. The method for preparing the polydimethylsiloxane super-hydrophobic anti-icing and de-icing material according to claim 2, characterized in that: In the step 3, the mass volume ratio of carbon nanotubes, 1H,1H,2H,2H-perfluorodecyltrimethoxysilane and anhydrous ethanol is 2.5g:0.8g:100mL, and the pH is adjusted to 3 with hydrochloric acid.
7. The method for preparing the polydimethylsiloxane super-hydrophobic anti-icing and de-icing material according to claim 2, characterized in that: In the step 3, the magnetic stirring time is 1 to 3 hours, and the ultrasonic time is 10 to 50 minutes.
8. The method for preparing the polydimethylsiloxane super-hydrophobic anti-icing and de-icing material according to claim 2, characterized in that: In the step 4, the solvent is n-hexane, the binder is polydimethylsiloxane, the polydimethylsiloxane is component A of Dow Corning 184-PDMS, and the curing agent is component B of Dow Corning 184-PDMS; The mass volume ratio of the total mass of the modified SiO2 nanoparticles and the modified carbon nanotubes to the n-hexane, the polydimethylsiloxane and the curing agent is 0.1 g:10 ml:0.1 g:0.01 g; and the magnetic stirring time is 1 to 3 hours.
9. The method for preparing the polydimethylsiloxane super-hydrophobic anti-icing and de-icing material according to claim 2, characterized in that: In the step 5, the curing temperature is 80° C. and the curing time is 1 to 2 hours.
10. An application of a polydimethylsiloxane super-hydrophobic anti-icing and deicing material, wherein the polydimethylsiloxane super-hydrophobic anti-icing and deicing material is prepared by the method for preparing the polydimethylsiloxane super-hydrophobic anti-icing and deicing material according to any one of claims 1 to 9, characterized in that: The polydimethylsiloxane super-hydrophobic anti-icing and de-icing material is used for hydrophobicity and anti-icing and de-icing on the surfaces of ships, airplanes, high-speed railways, and marine engineering projects.
Citation Information
Patent Citations
Preparation method of nanoparticles with photo-thermal conversion performance and photo-thermal super-hydrophobic sponge
CN116463108A
Photo-thermal super-hydrophobic porous material based on ultralight clay as well as preparation method and application of photo-thermal super-hydrophobic porous material
CN116673010A
Preparation method and application of super-hydrophobic photo-thermal film
CN117343386A
Cited By
Flexible anti-icing composite film with force and damage perception and preparation method thereof
CN119875182A
A flexible anti-icing composite membrane with force and damage sensing and its preparation method
CN119875182B
Preparation method of carbon nanotube cluster micro-nano composite photo-thermal super-hydrophobic anti-icing coating
CN119955378A
Water-based deicing coating and preparation method thereof
CN120272090A
Resin-based composite material with integrated anti-icing and wave-transparent functions as well as preparation method and application of resin-based composite material
CN120775219A